Depuración de aguas servidas, utilizando especies acuáticas, en la ciudad de Moyobamba - Rodríguez Chumbe, María Isabel (2012)
The study "Wastewater purification, using aquatic species, in Moyobambacity", aro se that in our region there are no experiences that have documented the use and exploitation of macrophytes on treatments for residential and industrial effluents. The objective of this research was to evaluate the efficiency of the Eichhornia crassipes and Pistia stratiotes species in removing pollutants present in the wastewater. T o achieve that goal will design a sewage treatment system with a hydraulic retention time of 8 days, where they were introduced the species mentioned in different times and separately; this research added a third treatment consisting of a partnership between the two species. The results obtained showed that Eichhornia crassipes ts more efficient in wastewatertreatment, achieving high removals in: 85.5 % in total coliforms, 77.7 Nitrates, 73.5 thermotolerant coliforms, DBOs,2o 66.1, Total Suspended Solids 60 %. Pistia stratiotes proved to be very susceptible to environrÍlental factors and the presence of pests, obtaining dismissals, where removals reached were: 67.1% phosphates, 65.6% nitrates, 63.8 % DBOs,20, 62.8 %Total Coliforms. With respect to the biomass behaviorof both . species, it was observed that a greater development ofthe root ofthe plant, where many times this was the double or triplt) the size of the aboveground biomass. As a final conclusion we can say that the domestic wastewater treatmentwith biological treatment, although. not widely known in our region, is a good innovative altemative low-cost and environmentally friendly. Key words: domestic wastewater treatment, biological treatment.